2009
DOI: 10.1111/j.1365-294x.2009.04336.x
|View full text |Cite
|
Sign up to set email alerts
|

Bi‐parental vs. cooperative breeding in a passerine: fitness‐maximizing strategies of males in response to risk of extra‐pair paternity?

Abstract: In socially monogamous species, males that risk cuckoldry more than others might gain inclusive fitness by yielding paternity to relatives. We tested this prediction in the Tibetan ground tit Pseudopodoces humilis, an unusual facultative cooperative breeder wherein most helpers (87% males) join a mated pair shortly before clutch completion. Extra-pair paternity among bi-parental broods occurred less often (26% of broods, 9% of young) compared with cooperative broods (68%, 25%). In the former, most extra-pair s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
57
2
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(62 citation statements)
references
References 46 publications
(69 reference statements)
2
57
2
1
Order By: Relevance
“…Both the ground tit [7], and the moustached warbler [8] exhibit variable mating systems, with some females breeding with more than one partner. However in these latter species, the formation of the polyandrous group differs from that of the dunnock.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Both the ground tit [7], and the moustached warbler [8] exhibit variable mating systems, with some females breeding with more than one partner. However in these latter species, the formation of the polyandrous group differs from that of the dunnock.…”
Section: Discussionmentioning
confidence: 99%
“…However in these latter species, the formation of the polyandrous group differs from that of the dunnock. While in dunnocks, the polyandrous males generally form the bond with the female at the beginning of the breeding season, in ground tits and moustached warblers, polyandrous group formation occurs after the female has initiated incubation [7], [8]. It seems reasonable that differences in adult sex ratio among these species (see discussion above) create scenarios in which males: (i) are constrained into forming breeding coalitions (e.g., as in dunnocks) and thus contribute more to paternal care; and (ii) have opportunities to breed monogamously (e.g., as in ground tits and moustached warblers), but when faced with perturbations, such as nest failures, can join another pair and try to secure residual reproductive success.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We used courtship behaviour and the brood patches of females to determine the gender of adult birds. We then validated these determinations from blood samples (Du & Lu , ). The sex of nestlings was also determined from blood samples.…”
Section: Methodsmentioning
confidence: 99%
“…The ground tit ( Parus humilis ) is a passerine inhabiting alpine meadows at 2500–5500‐m elevation throughout the Tibetan plateau. Our previous studies on a population in the northeast of the species’ range revealed that the annual turnover of individuals is very high (Du & Lu 2009). When breeding, the birds establish socially monogamous pairs, of which 20% are helped mainly by male individuals that fail to find a social mate or finish a nesting attempt during the breeding season.…”
Section: Introductionmentioning
confidence: 99%